Better than expected performance effect depends on the spatial location of visual stimulus - Soodeh Majidpour; Mehdi Sanayei; Reza Ebrahimpour; Sajjad Zabbah (Scientific Reports)
Abstract The process of perceptual decision-making in the real world involves the aggregation of pieces of evidence into a final choice. Visual evidence is usually presented in different pieces, distributed across time and space. We wondered whether adding variation in the location of the received information would lead to differences in how subjects integrated visual information. Seven participants viewed two pulses of random dot motion stimulus, separated by time gaps and presented at different locations within the visual field. Our findings suggest that subjects accumulate discontinuous information (over space or time) differently than when it is presented continuously, in the same location or with no gaps between them. These findings indicate that the discontinuity of evidence impacts the process of evidence integration in a manner more nuanced than that presumed by the theory positing perfect integration of evidence.